Clinical and cost effectiveness of a multi-professional medication reviews in care homes (CAREMED). (14th July 2020) - Desborough, James A; Clark, Allan; Houghton, Julie; Sach, Tracey; Shaw, Val; Kirthisingha, Viveca; Holland, Richard C; Wright, David J
Abstract: Objectives: With 70% of care home residents experiencing a medication error every day in the UK, better multi-professional working between medical practitioners, pharmacists and care homes was recommended. The aim of this study was to determine the effectiveness (falls reduction) and cost-effectiveness, of a multi-professional medication review (MPMR) service in care homes for older people. Method: A total of care homes in the East of England were cluster randomised to 'usual care' or two multi-professional (General practitioner, clinical pharmacist and care homes staff) medication reviews during the 12-month trial period. Target recruitment was 900 residents with 10% assumed loss to follow-up. Co-primary outcome measures were number of falls and potentially inappropriate prescribing assessed by the Screening Tool of Older Persons Prescriptions. Key findings: A total of 826 care home residents were recruited with 324 lost to follow-up for at least one primary outcome measure. The mean number of falls per resident per annum was 3.3 for intervention and 3.0 for control ( P = 0.947). Each resident was found to be prescribed 0.69 (intervention) and 0.85 (control) potentially inappropriate medicines after 12 months ( P = 0.046). No significant difference identified in emergency hospital admissions or deaths. Estimated unadjusted incremental mean cost per resident was £374.26 higher in the intervention group. Conclusions: In line with other medication review based interventions in care homes, two MPMRs improved medication appropriateness but failed to demonstrate improvements in clinical outcomes. From a health system perspective costs where estimated to increase overall and therefore a different model of medicines management is required.